2021
DOI: 10.1155/2021/1321289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Admission Hyperglycemia on Short-Term Prognosis of Patients with Non-ST Elevation Acute Coronary Syndrome without Diabetes Mellitus

Abstract: Objective. To evaluate the effect of admission hyperglycemia on the short-term prognosis of patients with non-ST elevation acute coronary syndrome (NSTE-ACS) without diabetes mellitus. Methods. The clinical data of 498 patients with NSTE-ACS admitted to the Department of Cardiology of the First Affiliated Hospital of Henan University of Science and Technology between March 2018 and November 2020 were analyzed. Based on the blood glucose (BG) level at admission, patients were divided into three groups: A ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Ten studies ( 8 , 27 35 ) reported short-term all-cause mortality, four studies ( 36 39 ) reported long-term all-cause mortality, and nine studies ( 6 , 7 , 40 46 ) reported both short- and long-term all-cause mortality, which were included in the primary meta-analysis. Eight studies ( 7 , 29 31 , 34 , 37 , 43 , 45 ) were also used for secondary outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies ( 8 , 27 35 ) reported short-term all-cause mortality, four studies ( 36 39 ) reported long-term all-cause mortality, and nine studies ( 6 , 7 , 40 46 ) reported both short- and long-term all-cause mortality, which were included in the primary meta-analysis. Eight studies ( 7 , 29 31 , 34 , 37 , 43 , 45 ) were also used for secondary outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Severely elevated glucose levels were significantly associated with MACEs compared with mildly to moderately elevated glucose levels. Higher blood glucose levels at admission were associated with higher incidence of multivessel disease ( 7 ) and acute kidney injury ( 30 , 34 ), larger infarct size ( 30 ), lower initial success rate of primary PCI ( 7 ), and worse post-PCI TIMI flow grades ( 31 )—degree of flow filling the distal coronary bed. Most events in MACEs were driven by in-hospital mortality ( 30 ) and heart failure ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Sauer et al [22] showed an increased risk of ventricular rhythm disorders with morphine administration in patients with STEMI. Furthermore, the studies of Tran et al [23] and Liu et al [24] suggested an increased risk of rhythm disorders with hyperglycemia in patients with NSTE-ACS.…”
Section: Discussionmentioning
confidence: 99%